Hubungan antara Olahraga dan Stres dengan Tingkat Hipertensi Pada Lansia - Festy Ladyani; Arti Febriyani; Toni Prasetia; Ica Berliana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Hypertension is an increase in blood pressure, one of the factors that affect hypertension, namely exercise and stress. The aim is to find out whether there is a relationship between exercise and stress and hypertension levels in the elderly. Method; this type of analytic observation research using a cross-sectional study approach. This research was conducted in October 2019. The population in this study were all elderly who were in the Tresna Werdha Natar Social Institution, totaling 78 people. The analysis used was univariate and bivariate analysis using the Chi-square test. Result; showed a significant relationship between the level of hypertension with exercise (p = 0.010) and stress (p = 0.002). There is a relationship between exercise and stress with the level of hypertension in the elderly at the Tresna Werdha Natar Social Home. Conclusion; that there is a relationship between exercise and stress on the incidence of hypertension in the elderly